Student Understanding In Using Google Classroom On Online Learning - Muhammad Azzarkasyi, (Jurnal Serambi Ilmu, 2024)
This study aims to determine students' understanding of using Google Classroom as an online learning medium at FKIP USM. The method used in this study is descriptive analysis with a quantitative approach and data analysis using percentages. The subjects in this study were students of the natural sciences (Physics, Mathematics, Biology, and Chemistry) environment FKIP Universitas Serambi Mekkah, amounting to 51 people. The instrument used in this study was a student understanding questionnaire. Based on the results of this study, there are 1 respondent (2%) who responds very high, 5 respondents (10%) responds high, 35 respondents (69%) responds moderately, 9 respondents (18%) responds low, and 1 respondent (2%) ) responds very low. Based on the results of research on student understanding in the use of Google Classroom in online learning, it can be concluded that it is good, this is evident from student data making it easier to store and access documents such as material or important assignments sent via Google Classroom, so that if students have not had time to print the required documents, they can access them first through Google Classroom. In addition, students are also facilitated to obtain announcements given by lecturers quickly (real time) so that they become effective and efficient in terms of time.